Are Usability Assessment Techniques Reliable in Non-Western Cultures? - Wee, Alvin Yeo (City University of Hong Kong, 2000)
This paper describes an exploratory study conducted to examine the efficacy of the global-software development lifecycle (global-SDLC), a Western software development approach employed to derive software for the global market. In the study, the global-SDLC was applied to adapt a US English spreadsheet for a non-Western market; in particular, the spreadsheet was adapted to accommodate Bahasa Melayu (Malaysia?s national language). Malaysians were recruited to evaluate the usability of the spreadsheet utilising three prevalent (Western originated) usability assessment techniques, namely, think aloud, questionnaire, and interview. The design and implementation phase of the global-SDLC were found to be efficacious. However, the results of the usability evaluation ?the last phase of global-SDLC? were found to be inconsistent. These inconsistencies may be attributed to the computer experience as well as the cultural attributes of the participants in the study. Implications of the findings and further work were also discussed.